The adventures of a girl called Bicycle - Uss, Christina (Margaret Ferguson Books, Holiday House, 2020)
Left at the Mostly Silent Monastery as a toddler and home-schooled by a retired nun, twelve-year-old Bicycle rides cross-country to meet a famous cyclist who she hopes will be her first friend.